2015
DOI: 10.1140/epjc/s10052-015-3735-8
|View full text |Cite
|
Sign up to set email alerts
|

Configurational entropy in brane-world models

Abstract: In this work we investigate the entropic information on thick brane-world scenarios and its consequences. The brane-world entropic information is studied for the sineGordon model and hence the brane-world entropic information measure is shown to be an accurate way for providing the most suitable range for the bulk AdS curvature, in particular from the informational content of physical solutions. Besides, the brane-world configurational entropy is employed to demonstrate a high organisational degree in the stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 48 publications
1
50
0
Order By: Relevance
“…In the recent years, many different examples appeared in the literature where there is a similar relation between the variation of the configurational entropy and the stability was shown to appear in as diverse systems as compact astrophysical objects [12] and holographic AdS/QCD models [5][6][7][8][9][10]. Many other recent applications of configuration entropy are found in the literature, as for example [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] The basis for the definition of the configuration entropy [1] is the information entropy of Shannon [28] that has the form − n p n log p n ,…”
Section: Introductionmentioning
confidence: 99%
“…In the recent years, many different examples appeared in the literature where there is a similar relation between the variation of the configurational entropy and the stability was shown to appear in as diverse systems as compact astrophysical objects [12] and holographic AdS/QCD models [5][6][7][8][9][10]. Many other recent applications of configuration entropy are found in the literature, as for example [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] The basis for the definition of the configuration entropy [1] is the information entropy of Shannon [28] that has the form − n p n log p n ,…”
Section: Introductionmentioning
confidence: 99%
“…Another interesting work about CE was presented in [46], where it is responsible for identifying the critical point in the context of continuous phase transitions. Finally, in braneworld scenarios it was shown that CE can be employed to demonstrate a high organizational degree in the structure of the system configuration for large values of a parameter of the sine-Gordon model [47]. The entropic information-measure in the context of f (R) braneworlds with non-constant curvature has also been studied [48].…”
Section: Introductionmentioning
confidence: 99%
“…[28], where the CE is responsible for identifying the critical point in the context of continuous phase transitions. Finally, in braneworld scenarios [29] it was shown that CE can be employed to demonstrate a high organizational degree in the structure of the system configuration for large values of a parameter of the sine-Gordon model.…”
Section: Introductionmentioning
confidence: 99%